Aplications of Vesicular Arbuscular Mycorrhizes (Vam) and Trichoderma Sp: Aplikasi Mikoriza Vesikular Arbuskular (MVA) dan Trichoderma Sp Dengan Umur Pindah Tanam Benih Jagung Ungu (Zea mays var Ceratina Kulesh). - Bibiana Rini widiati; Hadija; Muh. Izzdin Idrus (Jurnal Penelitian Pertanian Terapan, 2023)
Vesicular Arbuscular Mycorrhizae and Trichoderma sp are biological agents of microorganisms to assist in nutrient uptake, suppress pathogen populations, accelerate growth and increase crop yields. This research aimed to determine the effect of age transplanting seeds with the application of Mycorrhizal Arbuscula Vesicular and a dose of Trichoderma sp., which could increase the production of Purple Corn (Zea mays var Ceratina Kulesh). This research was carried out in an experiment using Split Plot Design. The Main Plot was the age of transplanting (m) with the application of Vesicular Arbuscular Mycorrhizae as much as 10 g.tan-1, which were: m1 (transplanting age 0 days), m2 (transplanting age 7 days), m3 (age of transplanting 10 days). The Sub-Plot (SP) was The Trichoderma sp. (t), which were: t0 (without Trichoderma sp.), t1 (Trichoderma sp. 100 g.tan-1), t2 (Trichoderma sp. 200 g.tan-1). Each treatment in the main plot and sub-plot was combined to create nine treatment combinations. Each treatment combination was repeated three times so that a total of 27 plot units. The results showed that the treatment of  10 days of transplanting with the application of Mycorrhizal Vesicular Arbuscula as much as 10 g.tan-1 gave the best results on cob diameter and Phosphorus uptake. Dosage of Trichoderma sp. 200 g.tan-1 gave the best results on planting crown weight, cob diameter, The combination of 10 days of transplanting, while the application of Vesicular Arbuscular Mycorrhizae and a dose of Trichoderma sp. 200 g.tan-1 gave the best results on cob weight per plant, Nitrogen and Potassium uptake.